Evaluación y manejo psicológico del paciente candidato a cirugía metabólica - Montt S., Denisse; Olguín V., Pablo; Marín L., Luciana; Cortés M., Susana (Revista Hospital Clínico Universidad de Chile, 2012)
Psychological factors can play a role in the onset, course and the way a patient copes with diabetes; therefore the mental health approach is gaining increasing relevance in the management of the disease. With the advent of metabolic surgery as a new treatment alternative, assessment of psychosocial variables and pre and postoperative psychological support acquire a significant role in the short and long term outcomes. The objective of this article is to highlight the importance of a proper assessment and treatment of behaviors and mental disorders that can interfere the adherence to post operatory directions, which is fundamental given the high prevalence of psychopathology in this population. The main psychological problems associated with this disease are presented, as well as psychosocial and behavioral domains assessed pre and post operatively. Patients must have realistic expectations regarding the surgery and be aware of their responsibility in the outcomes, committing themselves to change their lifestyle and self-care. Continuous follow up that includes psychological support and treatment if necessary is required.